Strategi Pencegahan Pernikahan Dini Selama Pandemi Covid-19 Di Kantor Urusan Agama Danau Kerinci - Nuzuli, Ahmad Khairul; Nizham, M.; Wahyudi, Ahmad (BINA' AL-UMMAH, 2023)
This study aims to explore early marriage prevention strategies implemented during the COVID-19 pandemic at the Danau Kerinci Religious Affairs Office (KUA). A qualitative approach with field research methods was used to understand the social dynamics that influence early marriage in the region. Data were collected through in-depth interviews, observation and documentation, with triangulation techniques to ensure data validity. Interviews were conducted with two main informants, namely Zulpadli, Penghulu Ahli Madya and Head of the KUA of Danau Kerinci Sub-district, and Sukardiman, a KUA administrator who plays an active role in managing early marriage cases. The results show that the rate of early marriage in Danau Kerinci Sub-district is relatively low due to the strict application of regulations by the KUA, including minimum age requirements and legality procedures through Religious Court approval. The main factor of early marriage in this area is low interest in learning, while economic factors and pregnancy outside marriage have little influence. Prevention strategies were implemented through socialization programs such as marriage advice, religious counseling and community activities, which significantly increased community awareness. This research makes a practical contribution to developing more adaptive policies for early marriage prevention, both during emergency situations such as the pandemic and normal conditions in the future.